Understanding pathways to crime: can anomie theory explain higher crime rates among refugees? : current f from a Swiss survey - Simmler, Monika (European journal on criminal policy and research, 2017)
This study explores the extent to which the comparatively high crime rates among refugees in Switzerland can be explained once anomie theory is employed to take individual and social factors into account. The discrepancy between expectations and internalized goals on the one hand, and accessible legal opportunities on the other, may lead to heightened personal strain and anomic reactions such as innovation and deviance. This research tested this notion via statistical data and a survey of refugees in Switzerland. The results offer moderate support to anomie-centered explanations of crime among refugees.